AS DIFERENÇAS ENTRE OS ALUNOS: COMO OS PROFESSORES DE EDUCAÇÃO FÍSICA EXPLICAM-NAS - Sandro Carneiro Brito, Alex; da Conceição Cruz, Elizângela; Pereira Lima, Ivaldo; da Conceição Soares Monte, Maria; da Paz Sousa, Maria; de Jesus Soares de Mota, Teresinha; de Sousa Moura Teixeira, Cristiane (Revista Form@re - Parfor/UFPI, 2026)
.